Sosialisasi Perhitungan Dan Penyetoran Pajak Umkm Di Kelurahan Tambunan, Kecamatan Makale Utara - Olivia Devi Yulian P; Lisa Kurniasari W; Mince Batara; Isak Pasulu; Althon K. Pongtuluran (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
This activity was carried out to provide information regarding taxation to MSMEs to increase the level of tax compliance which is not yet optimal in Indonesia. Socialization and demonstration methods as well as practice calculating and paying taxes using case studies, and question and answer methods are carried out in this activity. Apart from that, it also provides an understanding not to be afraid to report taxes and socializes the impacts that arise when MSMEs do not pay taxes. This activity was attended by local people who have small businesses in their homes selling handicrafts, basic necessities, food and drinks, etc. The results of this socialization found that many MSME actors still do not understand how to deposit MSME Income Tax due to their limited knowledge